Roman Britain - O'Connell, Martin (England Wayland Publishers Ltd, 1989)
Uses the clues discovered by archaeologists to recreate everyday life in Roman Britain for soldier and civilian alike. Suggested level: intermediate, secondary.
Include Color Illustration, Glossary and Index
Keywords: Romans -- England